The Influence of Transformational Leadership Style in Improving The Motivation and Performance of Employees of Perumda Pasar Juara Bandung City - Ferlino, Ricky; Mulyasana, dedi; Indah, Diani (Journal of Management, 2025)
Human resources have an important role both in terms of ability and performance in achieving company goals, especially in the Pasar Juara Regional Public Company in Bandung City. In this study, the author uses a quantitative descriptive analysis study method. The quantitative analysis used is a multiple linear statistical model using independent variables and dependent variables. In this study, there are 3 (three) variables used by the author, consisting of 2 (two) independent variables in this case "transformational leadership style" (X1), "motivation" (X2) while the dependent variable is "employee performance" (Y). Regarding the role of transformational leadership style and motivation on employee performance, it is inseparable from the discussion on the influence of independent variables (X1 and X2) on the dependent variable (Y) and the relationship between the three variables, both partially and simultaneously.